2019
DOI: 10.4196/kjpp.2019.23.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the glycine response by serotonin on the substantia gelatinosa neurons of the trigeminal subnucleus caudalis in mice

Abstract: The lamina II, also called the substantia gelatinosa (SG), of the trigeminal subnucleus caudalis (Vc), is thought to play an essential role in the control of orofacial nociception. Glycine and serotonin (5-hydroxytryptamine, 5-HT) are the important neurotransmitters that have the individual parts on the modulation of nociceptive transmission. However, the electrophysiological effects of 5-HT on the glycine receptors on SG neurons of the Vc have not been well studied yet. For this reason, we applied the whole-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The increase in the chloride conductance hyperpolarizes the postsynaptic cell and can inhibit the neuronal firing . Many agents, such as alcohol, anesthetics, steroids, serotonin, Zn 2+ , and tropeines, have been found to have an important role in modulating the function of glycine receptors. , BPA, a component of polycarbonate plastic utilized in food and beverage containers and in some dental material, is also an endocrine disruptor and has been demonstrated to be an effector of a great number of ion channels, such as voltage-gated Ca 2+ channels, voltage-gated Na + channels, large-conductance Ca 2+ /voltage-activated K + (BK) channels, nicotinic receptors, estrogen receptor, and GABA receptors. ,, To the best of our knowledge, this is the first report to identify a positive correlation between glycine and BPA in the SG neurons of the Vc in mice. Through electrophysiological study, we showed that BPA induced potentiation on the glycine receptor-created responses (except in the early neonatal 0–3 postnatal days) through activation of heteromeric glycine receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in the chloride conductance hyperpolarizes the postsynaptic cell and can inhibit the neuronal firing . Many agents, such as alcohol, anesthetics, steroids, serotonin, Zn 2+ , and tropeines, have been found to have an important role in modulating the function of glycine receptors. , BPA, a component of polycarbonate plastic utilized in food and beverage containers and in some dental material, is also an endocrine disruptor and has been demonstrated to be an effector of a great number of ion channels, such as voltage-gated Ca 2+ channels, voltage-gated Na + channels, large-conductance Ca 2+ /voltage-activated K + (BK) channels, nicotinic receptors, estrogen receptor, and GABA receptors. ,, To the best of our knowledge, this is the first report to identify a positive correlation between glycine and BPA in the SG neurons of the Vc in mice. Through electrophysiological study, we showed that BPA induced potentiation on the glycine receptor-created responses (except in the early neonatal 0–3 postnatal days) through activation of heteromeric glycine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The method to prepare the brain slices was similar to that in our previous study . ICR mice with suitable experimental ages were chosen randomly (early neonatal: 0–3 postnatal days, juvenile: 7–20 postnatal days, and adults: 45–60 postnatal days).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation